Efficient parallel out-of-core matrix transposition. (6th February 2006) - Krishnamoorthy, Sriram; Baumgartner, Gerald; Cociorva, Daniel; Lam, Chi-Chung; , P. Sadayappan
This paper addresses the problem of parallel transposition of large out-of-core arrays. Although algorithms for out-of-core matrix transposition have been widely studied, previously proposed algorithms have sought to minimise the number of I/O operations and the in-memory permutation time. We propose an algorithm that directly targets the improvement of overall transposition time. The I/O characteristics of the system are used to determine the read, write and communication block sizes such that the total execution time is minimised. We also provide a solution to the array redistribution problem for arrays on disk. The solutions to the sequential transposition problem and the parallel array redistribution problem are then combined to obtain an algorithm for the parallel out-of-core transposition problem.